Withholding and withdrawing life-support in adults in emergency care: joint position paper from the French Intensive Care Society and French Society of Emergency Medicine - Jean Reignier; Anne-Laure Feral-Pierssens; Thierry Boulain; Françoise Carpentier; Pierrick Le Borgne; Denis Del Nista; Gilles Potel; Sandrine Dray; Delphine Hugenschmitt; Alexandra Laurent; Agnès Ricard-Hibon; Thierry Vanderlinden; et al. (Annals of Intensive Care, 2019)
Abstract For many patients, notably among elderly nursing home residents, no plans about end-of-life decisions and palliative care are made. Consequently, when these patients experience life-threatening events, decisions to withhold or withdraw life-support raise major challenges for emergency healthcare professionals. Emergency department premises are not designed for providing the psychological and technical components of end-of-life care. The continuous inflow of large numbers of patients leaves little time for detailed assessments, and emergency department staff often lack training in end-of-life issues. For prehospital medical teams (in France, the physician-staffed mobile emergency and intensive care units known as SMURs), implementing treatment withholding and withdrawal decisions that may have been made before the acute event is not the main focus. The challenge lies in circumventing the apparent contradiction between the need to make immediate decisions and the requirement to set up a complex treatment project that may lead to treatment withholding and/or withdrawal. Laws and recommendations are of little assistance for making treatment withholding and withdrawal decisions in the emergency setting. The French Intensive Care Society (Société de Réanimation de Langue Française, SRLF) and French Society of Emergency Medicine (Société Française de Médecine d’Urgence, SFMU) tasked a panel of emergency physicians and intensivists with developing a document to serve both as a position paper on life-support withholding and withdrawal in the emergency setting and as a guide for professionals providing emergency care. The task force based its work on the available legislation and recommendations and on a review of published studies.